2022
DOI: 10.11646/zootaxa.5195.2.2
|View full text |Cite
|
Sign up to set email alerts
|

A new species of bush frog (Anura, Rhacophoridae, Raorchestes) from southern Xizang, China

Abstract: Based on molecular evidence and morphological data, we describe a new species Raorchestes yadongensis sp. nov. from Yadong County, Xizang Autonomous Region, China. The new species can be distinguished based on a combination of the following characters: (1) small body size, SVL 17.8–24.1 mm in adult males; (2) head wider than long; (3) eye diameter about three times as much as tympanum diameter; (4) tympanum distinct; (5) fingers with rudimentary webbing and narrow lateral dermal fringes; relative finger length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…This region is extremely unique and deserves our continued attention. In recent years, many new species have been gradually discovered in this area ( Jiang et al 2012 , 2016a , 2016b , 2016c ; Shi et al 2020 ; Che et al 2020 ; Zhang et al 2022 ). There is also high species diversity in the middle and lower reaches of the Yarlung Zangbo Grand Canyon, for example, Mahony et al (2018) revealed cryptic diversity within the Megophrys major species group, which suggests that the species diversity in this area may have been previously underestimated and therefore needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This region is extremely unique and deserves our continued attention. In recent years, many new species have been gradually discovered in this area ( Jiang et al 2012 , 2016a , 2016b , 2016c ; Shi et al 2020 ; Che et al 2020 ; Zhang et al 2022 ). There is also high species diversity in the middle and lower reaches of the Yarlung Zangbo Grand Canyon, for example, Mahony et al (2018) revealed cryptic diversity within the Megophrys major species group, which suggests that the species diversity in this area may have been previously underestimated and therefore needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two years, several field surveys were conducted in this area and specimens of the family Megophryidae were collected. Also, a new bush frog, Raorchestes yadongensis Zhang, Shu, Liu, Dong, & Guo, 2022, was recently found and described ( Zhang et al 2022 ). Based on morphological comparison and molecular phylogenetic analyses, some specimens were identified a new member of Xenophrys .…”
Section: Introductionmentioning
confidence: 99%